Point-of-care ultrasonography (POCUS) in hemophilia A: a commentary on current status and its potential role for improving prophylaxis management in severe hemophilia A. (April 2017) - Acharya, Suchitra S.; Rule, Brittny; McMillan, Omar; Humphries, Thomas J.
In patients with severe hemophilia A, recurrent bleeding into joints results in increased morbidity and reduced quality of life. Prophylaxis using replacement factor products, especially when initiated early, has established benefits in terms of reducing joint bleeds and preserving joint function. Poor adherence to prophylactic regimens is a common cause for breakthrough bleeds and resultant arthropathy. Improving prophylaxis management, especially in the transitional age group, is a challenge. Here, we discuss the current status of ultrasonography (US) in hemophilia A, challenges in its wider implementation, and the potential for use of point-of-care US (POCUS) as an adjunct in the routine management of patients with hemophilia following prophylaxis regimens. Using POCUS, in which US is performed by trained hematologists and nonphysician operators (rather than comprehensive US performed by imaging specialists), specific clinical questions can be addressed in a time-efficient, user-friendly manner to promote adherence to prophylaxis and guide or modify treatment approaches. This review also discusses barriers to acceptance of POCUS as a part of routine management of patients with hemophilia, including questions related to its diagnostic accuracy, dependence on trained operators, agreement on appropriate scoring systems, and potential usefulness in patient management.